Shigellosis in children less than five years in urban slum area: a study at primary health care in Jakarta - Junita Elvira; Agus Firmansyah; Arwin A. P. Akib (Paediatrica Indonesiana, 2007)
Background Shigellosis has a global distribution especially incountries with poor hygiene and sanitation. The most commonmanifestation of shigellosis in children is diarrhea with broadspectrum manifestations from watery diarrhea to classicaldysentery. Appropriate antibiotic management is important toeradicate Shigella spp.Objective To find out shigellosis prevalence and manifestationsand also Shigella spp. resistance pattern in children less than 5years with acute diarrhea in certain district urban slum areas inJakarta.Methods This cross sectional study involved 475 outpatients ofless than 5 years old with acute diarrhea who visited primary healthcares in Jakarta from July– October 2005. Stool for culture andantibiotic resistance test was taken with single rectal swab.Results Shigella spp. was found only in 3 (0.6%) patients. Thesubjects were between 6 to 24 months. Watery diarrhea was foundin 1 subject and so was the classical dysentery manifestation offever and bloody diarrhea. Two strains were found, 2 cases of S.sonnei and 1 case of S. flexneri. They were resistance tocotrimoxazole, tetracycline, and colistine.Conclusion Shigella spp. was not the main cause of acute diarrheain children less than 5 years old. Due to the small number ofcases, we could not find the most common manifestation andresistance pattern of shigellosis in these children.